Prototipe Sistem Deteksi Jarak Kendaraan Roda Empat Untuk Mengurangi Angka Kecelakaan Berbasis Arduino - Arief Rahman Wahid; Khozainuz Zuhri; Fatimah Fahurian (Jurnal Teknologi dan Informatika (JEDA), 2022)
Based on the research, we need a technology that can be used to monitor the distance when driving in order to reduce the rate of road accidents. The purpose of the author is to make a device on vehicles using Arduino. So the author makes a solution with a report entitled" Design and build a distance detection device on cars to reduce the number of accidents in Lampung based on Arduino". This tool utilizes an ultrasonic sensor as a distance reader,so that the driver can determine the distance between the vehicle and the object in front or behind the vehicle. Based on the results of research that has been tested using the Black box testing method, and the use of the device is in accordance with the function.